HPLC Determination of Satranidazole in Bulk and Pharmaceutical Dosage Forms - NATARAJAN, SUNDER; RAMAN, BHANU (Asian Journal of Chemistry, 2010)
A simple, fast, sensitive, specific, precise, accurate and rugged stability indicating reverse phase high performance liquid chromatographic method has been developed and validated for the estimation of satranidazole in bulk material and in formulations. The stability indicating capability of the method was proven by subjecting the drugs to ICH stress conditions of alkaline and acidic hydrolysis, oxidation, photolysis and thermal degradation and resolution of the degradation products formed therein. The specificity was confirmed by spiking process related impurities of satranidazole and their separation from the main peak. The separation was obtained using a mobile phase of mixture of pH 3.0 buffer and acetonitrile in the ratio 600:400 with final pH of 3.6 on a ODS column (4.6 mm × 250 mm, 5 μ) with UV detection at 250 nm at 1 mL/min flow rate. For stress studies, a diode array detector was used. The elution of satranidazole was at 4.77 min. The linear dynamic range was 60 mcg/mL to 240 mcg/mL for satranidazole. Percentage recoveries for satranidazole was 99.64 %.